Eksplorasi Limbah Kulit Kopi Ekselsa sebagai Pewarna Alam Tekstil pada Serat Rami - Rahmawati, Evi Febri; Titisari, Bintan (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
Ekselsa coffee (Coffea liberica var. dewevrei) is taxonomically classified in the same category as Liberika coffee and other Liberoid species. The ekselsa coffee production in the Ngrayudan area, Jogorogo, Ngawi Regency, East Java produces two tons of ekselsa coffee as their superior products, with 40% coffee husk waste in one year. The coffee husk waste is currently used only as an animal feed. If not utilized properly, the waste can potentially pollute the surrounding environment. Therefore, this study aims to explore the potential of ekselsa coffee husk waste to be used as natural dyes for textiles as an alternative solution in utilizing coffee husk waste which has added value. Exploration of natural dyes was applied to natural fiber textiles, namely hemp fiber (Boehmeria nivea) because hemp fiber has a high absorption capacity. In addition, hemp fiber has properties similar to cotton fiber, so hemp cloth can be used as an alternative to cotton cloth in the future. The research method was a qualitative method, namely literature studies, observations and interviews on coffee processing in Ngawi Regency, as well as exploration of coffee husk waste as a natural dye in textiles. The exploration was carried out by extracting natural dyes from the waste of ekselsa coffee husks and conducting experiments with four types of mordant and four methods of mordanting on hemp fiber. The types of mordant used were alum, vinegar, quicklime and tunjung, and the mordanting methods used were pre mordanting, simultaneous mordanting, post mordanting and pre post mordanting methods. From the exploration results, it can be concluded that ekselsa husk waste can produce color variations with shades of brown, cream and gray depend on the mordant on hemp fiber. In addition to providing color variations, the use of mordant can also increase the level of color fastness in textiles.